ANALISIS RADIONUKLIDA 137Cs DI DALAM PELAT ELEMEN BAKAR NUKLIR U3Si2/Al DENSITAS 4,8 gU/cm3 BURN UP 60% PASCA IRADIASI MENGGUNAKAN METODE KLOROPLATINAT - Nugroho, Arif; Sutriah, Komar; Mulijani, Sri; Basuki, Triyono; Ade Rofiqi, Ahmad; Boybul; Noerpitasari, Erlina; Kriswarini, Rosika; Carlos Sihotang, Juan; Jamaludin, Agus (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Analysis of 137C isotopes in post-irradiation nuclear fuel is vital in determining burn up and fuel behavior during fission. The 137Cs isotope is used as input data for burn up calculations because it has a long half-life (30.17 years) and a large fission yield (6.026%). This study uses the chloroplatinate precipitation method to separate the 137Cs isotope from U3Si2/Al nuclear fuel with a density of 4.8 gU/cm³ with a burn up of 60% after irradiation. The separation process begins with cutting and dissolving the fuel sample, followed by the addition of CsNO₃ as a carrier solution and H₂PtCl₆ reagent to form Cs₂PtCl₆ precipitate. The results of the analysis using gamma spectrometry showed that the spectrum of the Cs₂PtCl₆ precipitate had the highest peak area of ​​67.6298 cps compared to the brown residue of 0.9165 cps and the supernatant of 0.2450 ​​cps. In addition, the results of this study showed an increase in the separation recovery value from 70% to 96.39%, which indicates the success of the separation of the 137Cs isotope from the U3Si2/Al fuel solution with a density of 4.8 gU/cm3 using the chloropaltinate precipitation method. The results of elemental mapping of the Cs₂PtCl₆ precipitate using SEM (scanning electron microscope) showed an even distribution of platinum (Pt), cesium (Cs), and chlorine (Cl) components, which shows the efficiency of this precipitation method. In addition, EDS (energy dispersive X-ray spectroscopy) analysis shows the elemental composition of the Cs₂PtCl₆ deposits. The three main elements identified are Pt, Cl, and Cs. The results of this study can provide an essential contribution to evaluating the performance of U3Si2/Al fuel with a density of 4.8 gU/cm3 after irradiation. They can be used for further research on Cs isotopes.